Karakteristik Campuran AC – WC Dengan Bahan Tambah Abu Tongkol Jagung - Bram Wisnu; Rais Rachman; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
This research to know and the characteristics of the influence of a mixture of AC-WC with the additional ashes to a mixture that uses an aggregate of river leoran enrekang district and to overcome the problem of corn cobs waste. To get the characteristics of a mixture AC-WC used method of Marshall Test. The results of the Test Marshall AC-WC added a characteristic mix with the ashes corn corbs with average value of Stability 0%-2% : 949,25 kg – 988,52 kg, for VIM 0%-2% : 4,03% - 3,32%, to Flow 0%-2% : 3,09 mm – 3,36 mm, to VMA 0%-2% : 21,61% - 20,97%, and finally VFB 0%-2% : 81,36% - 84,18%. According to the levels of a study from the 0%-2% ashses corncobs meet general Specification of Bina Marga 2018.